Pengaruh Kepercayaan dan Kualitas Website (Webqual) terhadap Keputusan Pembelian Tiket Kereta Api melalui Aplikasi KAI Access di Surabaya (FAKULTAS ILMU ADMINISTRASI UNIVERSITAS DR SOETOMO SURABAYA, 2023)
The purpose of this study is to determine and analyze the influence of trust and website quality on train ticket purchase decisions through the KAI Access application both simultaneously and partially as well as to determine the dominant variables on purchasing decisions. This research is quantitative research with a causal type of research. The results of this study show that the trust and quality of the website simultaneously affect the purchase decision at KAI Access in the city of Surabaya, with a test value of F-calculated. greater than ,F-table. That is with a value of 77,196 greater than 3,089. The trust variable partially affects the purchase decision on the KAI Access Application with a value of ,t-calculate. greater than ,t-table. which is 2,806 greater than 1,984. Website quality variables are the dominant variables that influence purchasing decisions on the KAI Access application with a value of ,t-calculate. greater than ,t-table. which is 6,302 which is greater than 1,984. While the website quality variable (,X-1.) that obtains the value of ,t-calculate. 6.302 is greater than the value of ,t-count. from the trust variable (,X-1.) which is 2,802 so that the website quality variable (,X-2.) is said to have a dominant influence on purchasing decisions (Y). The variables trust (,X-1.) and website quality (,X-2.) have an influence of 72.7% on purchasing decisions (Y). This is evidenced by the value of R Square, which is 0.727. While the rest (100% - 72.7% = 27.3%) are influenced by other variables outside the variables not studied by the author.